Exiled at home: British Muslims’ experiences of integration - Elsayed, Sara (Frontiers in Sociology, 2023)
This article takes up the question of Muslim integration in the UK with one main argument: British Muslims, including those who are UK-born, endure wider exilic narratives that stand in clear contradiction to a rooted sense of belonging and equal citizenship. Referring to data from 12 months of ethnographic research, this article argues that integration as a lived experience for this community is ironically characterised by a range of exilic narratives entailing stereotyping, misrecognition, misrepresentation, and inequalities that put their sense of Britian as 'home' at stake. While these conditions do not necessarily work in the same way for all Muslims across their differences, they generally shape --in many different ways--their perceptions and understandings of belonging, home, and integration. Exploring everyday integration practices and dynamics in a local community, this paper discusses Muslims' sense of belonging and the barriers they encounter in achieving a sense of home. It investigates the roles of fear and citizenship built in inequalities in creating an exilic space that impinges on Muslims' sense of belonging. The analysis at the end extends this to highlight the responses and approaches Muslims adopt in their efforts to construct belonging in an exilic context.